THE EFFECTIVENESS OF PROCYANIDIN ON RED GRAPE SEED EXTRACT IN TREATMENT OF PERIODONTITIS INDUCED BY DIABETES MELLITUS - Rachmawati, Ranny; Handoko, Monica Annasthasia; Avrilia, Isabella; Wisnawati, Angela Latisha (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2024)
Introduction: Periodontal disease, including periodontitis, ranks as the 6th complication for Diabetes Mellitus. Research has found an increase of inflammation and higher alveolar bone loss in the periodontal of diabetes mellitus patients. One of the components which exhibited multiple bio-activities like anti oxidative, anti-inflammatory, antidiabetic antimicrobial cardioprotective, neuroprotective, immunomodulatory, and anti-obesity activities is procyanidin. Procyanidin can be found in various natural ingredients and one of the most abundant compositions is found in red grape seeds. Methods: The method used in this study is a literature review from several academic databases including : Google Scholar, PubMed, Mendeley, Wiley, and the university's online library with boolean searching method. Results: The several articles used in this literature review show that the protective effect of grape seed procyanidin plays a role in attenuating the increase of MFG-E8, suppressing the increase of IL-1beta protein level, improving HOMA-IR and insulin levels in diabetes, increasing IL-10 and TGF-beta accumulation in the gingival epithelium of periodontitis condition, and MMP- and HIF-1alpha immunohistochemistry showed an increase in its levels for periodontitis with diabetes rats, but decreased as grape seed procyanidin extract (GSPE) was administered. Conclusion: The present study suggested that procyanidin in grape seed extract played a role in treating periodontitis in diabetes patients through its anti- inflammatory role and its ability to decrease alveolar bone loss. There are still very few studies regarding this topic, therefore